2022
DOI: 10.3390/ijerph19031579
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition and Physical Fitness: Does This Relationship Change in 4 Years in Young Adults?

Abstract: (1) Background: There are few studies investigating the relationship between physical fitness and body composition in young adults and, to our knowledge, there are no such reports focusing specifically on physiotherapy students. This observational study aimed to assess the relationship between physical fitness and selected anthropometric measurements as well as body composition in Polish students in the first year and in the final year of a university course in physiotherapy. (2) Methods: A group of 100 random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The analysis also revealed that only in folk dancers, but not in ballroom dancers, the BMI correlates very strongly and positively with the dancing experience. This is quite an interesting result and should be the subject of future research considerations taking into account folk dancers' body composition to investigate whether this very strong and positive correlation between BMI and dancing experience is related to developed muscle or fat mass [54]. From a practical and clinical point of view, understanding the relationship between practicing particular forms of dance and body posture, low back pain and spine mobility may allow dance instructors to optimize the training process and sensitize them to specific musculoskeletal overuse pathologies, as well as reduce the risk of future musculoskeletal injuries.…”
Section: Discussionmentioning
confidence: 76%
“…The analysis also revealed that only in folk dancers, but not in ballroom dancers, the BMI correlates very strongly and positively with the dancing experience. This is quite an interesting result and should be the subject of future research considerations taking into account folk dancers' body composition to investigate whether this very strong and positive correlation between BMI and dancing experience is related to developed muscle or fat mass [54]. From a practical and clinical point of view, understanding the relationship between practicing particular forms of dance and body posture, low back pain and spine mobility may allow dance instructors to optimize the training process and sensitize them to specific musculoskeletal overuse pathologies, as well as reduce the risk of future musculoskeletal injuries.…”
Section: Discussionmentioning
confidence: 76%
“…The total score of this index can be analyzed by referring to the norms developed for age-specific groups, separately for males and females. A detailed description and evaluation of this index have been described in previous studies [ 23 , 24 ]. In this study, the endurance trial was abandoned.…”
Section: Methodsmentioning
confidence: 99%
“…Assessing body tissue parameters, such as lean body mass and body fat, as well as body water, is important for a number of reasons. The most common research is to establish an appropriate diet, examine the effects of exercise, select the appropriate training (including physiotherapy) and establish developmental norms [9].…”
Section: Analysis Of the Literaturementioning
confidence: 99%